Defect-Controlled, Scalable Layer-by-Layer Assembly of High-k Perovskite Oxide Nanosheets for All Two-Dimensional Nanoelectronics - Yim, H.; Yoo, S.Y.; Kim, Y.H.; Chae, K.H.; Kim, Y.-H.; Kim, S.K.; Baek, S.-H.; Lee, C.-H.; Choi, J.-W. (American Chemical Society, 2021)
Two-dimensional (2D) nanosheets hold great promise as a material platform in the next-generation electronic and optoelectronic devices due to their wide tunability in physical and chemical properties, outstanding electrical, and mechanical stability. However, their extensive application in practical devices have been seriously limited by the absence of large-area fabrication technology with defect control capability and good spatial uniformity. Here, we report a general strategy to obtain large-area, defect-controlled high-k dielectric films via scalable layer-by-layer assembly of single-crystalline perovskite oxide nanosheets for all-2D field-effect transistors (FETs). In particular, a new material design for Dion-Jacobson-type Sr1.8Bi0.2Nb3O10 nanosheets was carried out to obtain high dielectric permittivity. In addition, a large-area (4 cm × 4 cm) fabrication of multilayered Sr1.8Bi0.2Nb3O10 nanosheet films with high uniformity and low defects is demonstrated using a layer-by-layer assembly process based on Langmuir-Blodgett method. By applying the high-k 2D multilayer Sr1.8Bi0.2Nb3O10 film as a gate dielectric, sub-1-V operating MoS2 FETs with a high field-effect mobility of ∼60 cm2 V-1 s-1 and an on/off ratio of 105 were demonstrated. These results envision that the proposed strategy to obtain large-area, high-k nanosheet films may enable the realization of all-2D nanoelectronics with high electrical performance, low voltage operation, and excellent stabilities. ？ 2021 American Chemical Society.